Wyznaczniki skuteczności terapii przestępców seksualnych wykazujących cechy niepełnosprawności intelektualnej = Determinants of effectiveness of the therapy of sex offenders who display intellectual disability features - Pospiszyl, Kazimierz (1938- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article presents recommendations for both the diagnosis and therapy of sex offenders with low intellectual capacity. Although this group requires separate diagnostic methods, the same therapeutic methods can be used with them as the ones which are effective for offenders without intellectual difficulties. The sexual life of people with intellectual disabilities is more difficult and complicated than their functioning in other areas of life. In the case of sexual deviant behaviour, their social perception deteriorates, social ostracism increases and, at the same time, theirself-esteem decreases.
Keywords: metody diagnozy; metody terapii; Dawny Ja / Nowy Ja; Model Dobrego Życia; diagnosis methods; therapy methods; Old Me / New Me; Good Life Model